Synthesis of air-stable two-dimensional nanoplatelets of Ruddlesden–Popper organic–inorganic hybrid perovskites. Issue 18 (29th April 2020) - Cherusseri, Jayesh; Varma, Sreekanth J.; Pradhan, Basudev; Li, Jinxin; Kumar, Jitesh; Barrios, Elizabeth; Amin, Mohammed Zain; Towers, Andrew; Gesquiere, Andre; Thomas, Jayan
Abstract : A simple and facile method to synthesize nanoplatelets of 2D Ruddlesden–Popper perovskites is presented. The nanoplatelets exhibit excellent emission in the ultraviolet region and the photodetector fabricated using the nanoplatelets shows high photodetectivity. Abstract : We present a simple and facile method to synthesize nanoplatelets of 2D Ruddlesden–Popper (RP) perovskites of the type (CH3 (CH2 )3 NH3 )2 (CH3 NH3 )Pb2 I7 where n = 2. The 2D RP nanoplatelets are synthesized from bulk 2D RP crystals via a reflux pre-treatment mediated-ultrasonication method. The as-synthesized 2D RP nanoplatelets are highly air-stable even after two months of storage under an ambient atmosphere. The bulk 2D RP crystals and 2D RP nanoplatelets are characterized using X-ray diffraction, scanning electron microscopy, transmission electron microscopy, Kelvin probe force microscopy, UV-visible spectroscopy, X-ray photoelectron spectroscopy (XPS), photoluminescence, time correlated single photon counting measurement, etc . A significant blue shift in the ultraviolet-visible absorption spectrum, high photoluminescence in the UV region, and the modified work function of the nanoplatelets indicate a strong quantum confinement effect. The quantum confinement in the nanoplatelets is further confirmed using XPS. A photodetector fabricated using these 2D RP nanoplatelets exhibits a high photodetectivity of 3.09 × 10 10 Jones.